Unveiling the heterosis pattern of modern maize breeding in Southwest China through population structure and genetic diversity analysis - Peng Ma; Hua Zhang; Hongxia Shui; Xuecai Zhang; Xiuquan Wang; Shibin Gao; Haiying Zhang; Zhi Nie; Chunyan Qing; Tingqi Lu; Qihua Pang; Wenzheng Pei; et al. (BMC Plant Biology)
Abstract Maize (Zea mays L.) is an important food crop throughout the world and is also one of the earliest crops to use heterosis. In this study, we evaluated the genetic diversity, population structure, and selective sweep of 100 elite inbred maize lines collected from the current breeding program in Sichuan province, Southwest China, using 5,261,175 high-quality single nucleotide polymorphisms (SNPs). We discovered an abundance of genetic diversities and classified them into four groups. By combining kinship relationships, these groups were further divided into Tropic-local A, Improved-tropic, Tropic-local B, and Improved-local. Genomic differentiation was assessed using F st values (0.21–0.44) as well as genetic diversity (π = 6.07 × 10−4 − 6.61 × 10−4). We generated 900 (90 × 10) hybrids using 90 and 10 inbred maize lines from 100 diverse maize germplasms. All hybrids were evaluated for 10 traits in three replicate tests across two locations. We found that the patterns of G1 × G3, G1 × G4, G2 × G3, and G3 × G4 exhibited significant heterosis in yield-related traits and have been used in commercial breeding. In addition, we also explored the relationship between 10 traits of hybrid offspring and the number of heterozygous SNP. Under most heterosis modes, the best linear unbiased estimation (BLUE) value of the trait was highly consistent with the trend of deleterious SNPs, but there was a deviation in the G1 × G3 mode. Taken together, the results provide insight into the utilization of the current maize germplasm in Sichuan province to improve hybrid breeding.